Penerapan Digital Branding Melalui Pendekatan Penyuluhan, Pelatihan, dan Pendampingan Bagi Pelaku UMKM Kelurahan Medokan Semampir - Erni Dwi Zulfarida Solihiyah; Ika Sari Tondang (FKIP, Universitas Palangka Raya, 2023)
Development in the current era of globalization is highly dependent on the economic sector. The role of communities in economic development lies in the advancement of Micro, Small, and Medium Enterprises (MSMEs). MSMEs can also absorb labor, thereby improving the welfare of the community. Medokan Semampir Subdistrict has an active MSMEs activity.but MSMEs in Medokan Semampir Subdistrict also face challenges in managing their businesses, especially regarding technological mastery and the lack of product branding implementation. In response to these issues, an intervention was implemented through educational sessions, training programs, and mentoring sessions focused on Digital Branding, specifically encompassing copywriting and product photography